HAMZA HAKIMZODA NIYOZIY’S CREATIVE WORK ON WOMEN’S RIGHTS, FREEDOMS, AND GENDER EQUALITY (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article discusses the rights, freedoms, and the role of women in society, as well as issues of gender equality, social inequality,old beliefs, and religious superstitions in the works of Hamza Hakimzada Niyazi, a reformist intellectual. It highlights hisanalytical views on these topics, with a focus on the rights of women, the importance of education, and the fight against ignoranceand outdated customs.